2015
DOI: 10.1371/journal.pone.0116955
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Composition and Diversity via 16S rRNA Gene Amplicons: Evaluating the Illumina Platform

Abstract: As new sequencing technologies become cheaper and older ones disappear, laboratories switch vendors and platforms. Validating the new setups is a crucial part of conducting rigorous scientific research. Here we report on the reliability and biases of performing bacterial 16S rRNA gene amplicon paired-end sequencing on the MiSeq Illumina platform. We designed a protocol using 50 barcode pairs to run samples in parallel and coded a pipeline to process the data. Sequencing the same sediment sample in 248 replicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
146
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 295 publications
(151 citation statements)
references
References 45 publications
5
146
0
Order By: Relevance
“…A recent study comparing the Illumina and 454 platforms to study bacterial diversity via 16 S rRNA gene amplicons in sediments and soda lakes also found that both methodologies performed in a similar manner and that the general trends in alphadiversity were conserved with the exception of evenness estimates where correspondence between methods was low (Sinclair et al, 2015). It is known that the OTU clustering method can influence the estimates of diversity (Edgar, 2013;Flynn et al, 2015;Sinclair et al, 2015). We used the UPARSE algorithm, which offers an improved accuracy compared to other methods, resulting in fewer OTUs likely closer to the expected number of species in a community (Edgar et al, 2011).…”
Section: 5mentioning
confidence: 91%
See 3 more Smart Citations
“…A recent study comparing the Illumina and 454 platforms to study bacterial diversity via 16 S rRNA gene amplicons in sediments and soda lakes also found that both methodologies performed in a similar manner and that the general trends in alphadiversity were conserved with the exception of evenness estimates where correspondence between methods was low (Sinclair et al, 2015). It is known that the OTU clustering method can influence the estimates of diversity (Edgar, 2013;Flynn et al, 2015;Sinclair et al, 2015). We used the UPARSE algorithm, which offers an improved accuracy compared to other methods, resulting in fewer OTUs likely closer to the expected number of species in a community (Edgar et al, 2011).…”
Section: 5mentioning
confidence: 91%
“…No significant differences in Chao1, Shannon, and Simpson indices were found between platforms. A recent study comparing the Illumina and 454 platforms to study bacterial diversity via 16 S rRNA gene amplicons in sediments and soda lakes also found that both methodologies performed in a similar manner and that the general trends in alphadiversity were conserved with the exception of evenness estimates where correspondence between methods was low (Sinclair et al, 2015). It is known that the OTU clustering method can influence the estimates of diversity (Edgar, 2013;Flynn et al, 2015;Sinclair et al, 2015).…”
Section: 5mentioning
confidence: 94%
See 2 more Smart Citations
“…After raw amplicon sequencing data were demultiplexed into individual samples, sequence pairs were assembled using an in-house bioinformatic pipeline (94). The pipeline further removed sequences with missing primers and unassigned base pairs.…”
Section: Methodsmentioning
confidence: 99%